The Associations Between Socioeconomic Status, Caregivers' Depressive Symptoms, Children's Health‐Promoting Behavior, and Children's Physical Health: A Mediation Model. Issue 2 (June 2015) - Yoo, Joan P.; Chung, Grace H.; Lee, Sang‐Gyun
<x xml:space="preserve">Abstract</x> The aim of this study was to examine the mediating effects of children's health‐promoting behaviors on the association between socioeconomic status, caregivers' depressive symptoms, and children's physical health outcomes. We used the first wave of "Seoul Education and Health Welfare Panel." Data were collected from 820 fourth‐grade elementary and first‐year middle school students and their caregivers using self‐administered surveys. Structural equation modeling was employed to analyze the mediating effects of health‐promoting behaviors. Bias‐corrected bootstrap confidence intervals were used to test the mediating effect. The results showed that both low socioeconomic status and caregivers' depressive symptoms were negatively associated with a child's health‐promoting behaviors. Children's health‐promoting behaviors were positively associated with physical health. However, children's physical health was not significantly associated with socioeconomic status but was marginally associated with caregivers' depressive symptoms. We found that children's health‐promoting behaviors significantly mediated associations between both socioeconomic status and children's physical health and between caregivers' depressive symptoms and children's physical health. Based on the findings, we suggest the development and implementation of school‐based, health‐enhancement programs as a means to improve the general health of all children and to reduce health inequalities.